2016
DOI: 10.1177/0883073816630087
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Mild Type Leukoencephalopathy Caused by a Homozygous EARS2 Mutation

Abstract: Childhood leukoencephalopathies are a broad class of diseases, which are extremely rare. The treatment and classification of these disorders are both challenging. Nearly half of children presenting with a leukoencephalopathy remain without a specific diagnosis. Leukoencephalopathy with thalamus and brain stem involvement and high lactate (LTBL) is a newly described childhood leukoencephalopathy caused by mutations in the gene encoding a mitochondrial aminoacyl-tRNA synthetase specific for glutamate, EARS2 Magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…To date, 26 patients are reported with LTBL (12 by Steenweg et al (2012), one by Talim et al (2013), two by Taylor et al (2014), one by Biancheri et al (2015), one by Kohda et al (2016), one by Kevelam et al (2016), one by Danhauser et al (2016), one by Taskin et al (2016), one by G€ ung€ or et al (2016), two by Şahin et al (2016) and two by Pronicka et al (2016)), with our patient being the 26th reported patient. The phenotype of our patient fits the severe group of LTBL patients, mostly due to signs of perinatal presentation of the disease and rapid decline of her clinical status.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…To date, 26 patients are reported with LTBL (12 by Steenweg et al (2012), one by Talim et al (2013), two by Taylor et al (2014), one by Biancheri et al (2015), one by Kohda et al (2016), one by Kevelam et al (2016), one by Danhauser et al (2016), one by Taskin et al (2016), one by G€ ung€ or et al (2016), two by Şahin et al (2016) and two by Pronicka et al (2016)), with our patient being the 26th reported patient. The phenotype of our patient fits the severe group of LTBL patients, mostly due to signs of perinatal presentation of the disease and rapid decline of her clinical status.…”
Section: Discussionmentioning
confidence: 61%
“…The collective findings of symmetrical signal changes of the deep white matter (usually sparing the periventricular rim), thalami and brainstem together with increased lactate on MRS is the hallmark of LTBL. In patients described with either mild (Biancheri et al 2015;G€ ung€ or et al 2016;Taskin et al 2016;Şahin et al 2016) or severe disease (Steenweg et al 2012;Kevelam et al 2016), the clinical presentation appeared to correlate with the severity of neuroimaging at each stage of this biphasic disease. However, lesions of the main structures involved were not different between patients in each group of severity, except for the significant improvement without new lesions of brain MR/MRS associated with the mild-intermediate forms.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The same genetic mutations have shown to cause diseases with variable clinical course. 191 It is worthwhile to look for anatomical factors or patterns on MRI, which determine the variable clinical course in diseases caused by the same mutations. More comprehensive and descriptive imaging studies are available to achieve this.…”
Section: Aims and Outline Of The Thesismentioning
confidence: 99%